Dating Violance Pada Perempuan (Studi Pada Empat Perempuan Korban Kekerasan Dalam Hubungan Pacaran Di Universitas X) - Mayasari, Asnia; Rinaldi, Kasmanto (Sisi Lain Realita, 2017)
This research is generally intended to provide an overview of how the causes and forms of violence experienced by women in relationships with their partners, or the so-called courtship. In this study using qualitative research methods. This study shows that the causes of violence that occur in women due to the existence of patriarchal culture that developed in the community. In the relationship of courtship relationship that occurs there is a tendency that courtship is considered as a form of ownership of which arises instinct to regulate and master. So that the forms of violence that appear in this relation identify that women are as parties in the master by his partner. Beatings, threats, restraints, are the means used by their male partners in order to organize and master them. While it is recognized that women's economic dependency is fulfilled by their partners, the resulting form of violence identifies that it makes women weaker and has no strong bargaining position in relationships. Until the form of violence that resulted in women being the disadvantaged. This is one way to dominate a woman, the conscious and unconscious actors force others to do what they want by playing with the fear, feelings of guilt or pity of others in order to exercise their dominance over women.